PREVALENSI PENYAKIT TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS LASI KAB AGAM TAHUN 2022 - Athosra Athosra; Maisyarah Maisyarah; Eka Budi Satria; Adriani Suwito (HUMAN CARE JOURNAL, 2022)
Tuberculosis is one of the global health problems that is a control commitment in the SDGs program with a sufficient number of incidents every year. In the working area of the Lasi Health Center where in 2020 there were 14 cases of tuberculosis and in 2022 it increased to 16 cases and 86 suspected cases of tuberculosis. This study aims to describe efforts to prevent tuberculosis in the working area of the Lasi Health Center in 2022.This research is quantitative with a descriptive approach. The population in the working area of the Lasi Health Center is 6,830 people. Sampling using a proportional sampling technique with a sample size of 99 people. Data collection used a questionnaire and data analysis including univariate analysis. The results showed socio-cultural (69.7%), physical environment of the house (74.7%) The conclusion is that the physical environment of the house is at risk for TB incidents and there are still many people who do not take TB prevention efforts. It is hoped that TB officers at the Lasi Health Center will carry out TB prevention in the community